Моделювання оптимально-виробничо-галузевої структури сільського господарства України - Халатур, Світлана Миколаївна; Khalatur, Svitlana Mykolaivna; Khalatur, Svitlana; Khalatur, S. (Одеський національний університет, 2015)
У статті представлена оптимізована інтелектуальна система підтримки прийняття рішень, що застосовується при формуванні плану виробництва продукції рослинництва Охарактеризовано загальні підходи до оптимізації виробничої структури сільського господарства. The article presents the optimized intellectual decision support system used in the formation of the plant production plan. The general approaches to optimization of the agricultural production structure are characterized. The article presents an optimized intellectual decision support system, which is used in the development of a plan for the production of crops and livestock. The system includes a database, a knowledge base, as well as modules for modeling, optimization, decision analysis and conclusions. When solving the optimization problem, the specific values of the variables are obtained and they indicate which crops and animals should be grown, as well as the resources and how much they should be used to make the most use. The module for analysis and solution elimination indicates the inefficient use of agricultural resources, supports the ability to draw conclusions and recommendations for users. A retrospective of the development of modeling in agriculture was researched. The general approaches to optimization of agricultural production structure of Ukraine are described and optimality criteria are given in modern economic conditions. The economic-mathematical model of optimization of the industrial structure of the branch is developed.
Modeling of optimally production-branch structure of agriculture of Ukraine
( Халатур Светлана https://orcid.org/0000-0001-8331-3341 )
Keywords: виробнича структура; production structure; рентабельність; profitability; перспективне планування; perspective planning; економіко-математична модель; economic-mathematical model; критерій оптимальності; optimality criterion